THE PROBLEM OF STRESS IN THE FORMATION OF A CHILD'S PERSONALITY - Shirinova Bahoroy Ikmatillo qizi (Journal of new century innovations, 2022)
Annotation: This article examines the problem of stress in the formation of a child's personality. The concept of stress, negative, painful experiences or disappointments caused by difficulties, insurmountable obstacles, unfulfilled expectations, and the theory of Hans Selye, the originator of stress theory, are described.